1998
DOI: 10.1038/bjc.1998.658
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 6 in skeletal metastases from prostate cancer and other common human malignancies

Abstract: Summary Prostatic adenocarcinoma commonly metastasizes to bone. Unlike most other bony secondaries, the majority of skeletal prostatic metastases are osteoblastic rather than osteolytic i nature. Several growth factors which are known to stimulate bone formation are expressed in benign and malignant prostate cells. bi none has been specifically linked to osteoscierotic metastases. Bone morphogenetic proteins (BMPs) induce ectopic bone formation in vivo. We have reported previously that BMP-6 mRNA and protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 30 publications
2
88
0
1
Order By: Relevance
“…9 Primary tumours included prostate (n 13), lung (n 8), kidney (n 2), breast (n 5), colon (n 1) and uterus (n 1). In addition primary tumour was obtained for three of the patients with prostate secondaries from transurethral resection specimens.…”
Section: Previous Workmentioning
confidence: 99%
“…9 Primary tumours included prostate (n 13), lung (n 8), kidney (n 2), breast (n 5), colon (n 1) and uterus (n 1). In addition primary tumour was obtained for three of the patients with prostate secondaries from transurethral resection specimens.…”
Section: Previous Workmentioning
confidence: 99%
“…PDF expression in the prostate is regulated by androgens (Paralkar et al 1998). BMP-2 and BMP-6 were both identified in prostate cancers (Ide et al 1997, Autzen et al 1998, Thomas et al 1998a. Interest in the role they might play in the pathogenesis of bony metastases in prostate cancer is under investigation.…”
Section: Activin In Vivomentioning
confidence: 99%
“…Because BMP-6 activity has been suggested to correlate with the ability of the prostate cancer to establish bone metastasis, 6,7,12 we therefore analyzed our patient cohort, excluding those metastatic patients with their secondary lesion developed other than in bone, on whether increased BMP-6 activity could predict development of metastasis to bone. We found that, by Kaplan-Meier analysis, patients with primary prostate cancer expressing high level of BMP-6 and low level of noggin had a higher chance for the development of bone metastasis (Figure 4f, P ¼ 0.032), whereas patients with primary prostate cancer expressing high level of BMP-6 and low level of both noggin and sclerostin also had a higher chance for the development of bone metastasis (Figure 4g, P ¼ 0.028).…”
Section: Bmp-6 Noggin and Sclerostin Using Alone Could Not Predict Dmentioning
confidence: 99%